TINJAUAN HUKUM TERHADAP HAK ANAK DALAM PERKAWINAN BEDA AGAMA - Mohamad Mohamad Faisal Aulia; Amin Mukrimun (Program Studi Al-Ahwal Al-Syakhshiyyah, 2022)
The polemics and controversies of interfaith marriages in Indonesia are still due to the uncertainty of the laws governing them. The reality in the interfaith marriage community is that there is no legal certainty in it. This makes children born from interfaith marriages protected by the state as regulated in Law no. 23 of 2002 concerning Child Protection Article 1. Meanwhile, according to Islamic law a child can be said to be legitimate if he has a lineage with his father if he is born from a legal marriage, this makes the child can be called a legitimate child. This study uses a normative juridical method with a normative theological approach. This research is classified as library research. The results of this study indicate that according to the applicable positive law, namely Law Number 1 of 1974 concerning Marriage, it does not recognize interfaith marriages, so interfaith marriages cannot be legalized in Indonesia. Marriages of Muslim couples are registered at the Office of Religious Affairs (KUA) and marriages of non-Muslim religious couples are registered at the Civil Registry Office (KCS). Legal protection for children according to Islamic law is the fulfillment of all children's needs for the future. As contained in the QS. At-Thala verse 6, children will get education and health insurance, only if the child is born from an unregistered interfaith marriage then he only has a nasab relationship with his mother because interfaith marriage is an illegitimate marriage and will lead to adultery. Keywords: Interfaith Marriage; Legal Review; Children's Rights